P-125 Is an emergency really an emergency? a follow up study of an evaluation of urgent admission requests to a hospice. (1st March 2017) - Harry, Alice; Whyte, Graham; Carduff, Emma
Abstract : Introduction: Delivering 24/7 specialist palliative care is a national priority. A previous study looking at the urgent requests to the hospice, over 3 months, showed that over ¾ of appropriate admissions were admitted within 24 hours. Aim: To describe the characteristics of patients who were admitted following a request for emergency admission over a 3 month period. Methodology: This was a retrospective case note review of data for the 12 months prior to emergency admission, describing the events leading up to and the outcome of the admission. Results: Twenty-nine patients were included in the analysis. Of the 29 patients included, 34% were from the most deprived quintile. Ninety percent of emergency referrals and 100% of admissions had a malignant diagnosis. Forty-one percent of emergency admissions were for end-of-life care (EOLC). Sixty-six percent had a DNACPR before admission and 90% had an electronic key information summary. Seventy-five percent had at least 1 hospital admission in the previous year but only 1 patient was admitted from hospital. Patients being admitted for EOLC or by their GP had a shorter length of admission. Seventy-two percent died during the admission and 28% were discharged home and later died at home or in the hospice. No patients died in hospital. Conclusion: The emergency admissions to the hospice over these 3 months were genuine emergencies. Most of the patients were living in deprivation, meaning they are more likely to have multiple co-morbidities and social complexities. These emergency admissions to the hospice prevented admission to hospital and furthermore any of these patients dying in hospital. Anticipatory care planning was evident but further work needs done to explore the impact of deprivation, the reasons behind the lack of emergency requests for patients with non-malignant conditions and pathways for direct hospice transfer of acute front door hospital admissions where appropriate.